Clinical Language Expressions Practiced by Indonesian Counsellors - Sulaiman Samad; Husain Syam; Karta Jayadi (International Journal of Language Education, 2022)
This paper aims to explore the kinds of clinical language expressions practiced by Indonesian counsellors. This qualitative study applies purpose sampling of 17 key participants who are counsellors. The data for this study are taken from semi-structured interviews. The semi-structured interviews allow the flexibility of the researchers to prompt the questions. The findings of the data reveal that clinical language expressions begins with the expressions of the exploration of counselees, condition of counselees, the critical aspects of the counselling activities, empathy and sympathy. In addition, the research findings encounters he reasons of using particular language expressions such as comfortability, client condition, and the flow of the counselling activities. This study recommends that the comprehension of the clinical language expressions can assist the counsellors for the success of counselling activities. Since this study is limited to the key participants, the researchers recommends for further broader and comprehensive study with different geographical settings.